Sudut Pandang Anak dalam Perceraian Orang Tua: Telaah Literatur - Ulya Layyina; Novi Qonitatin; Haiyun Nisa (Universitas Airlangga, 2025)
Parental divorce is a transformative experience that profoundly affects children's lives. However, research has largely prioritized on adult perspectives, often marginalizing children's own experiences. This scoping review systematically examines the literature on children's voices in parental divorce to identify gaps and inform future practice. A systematic search of ScienceDirect, Scopus, and Google Scholar using the PRISMA-ScR guidelines identified 442 articles, of which six met the inclusion criteria. The findings indicate that children are not passive recipients but active agents who experience parental divorce with significant emotional complexity. Three consisten needs emerged: emotional support, honest and age-appropriate explanations about the divorce, and meaningfull opportunities for their voices to be heard and considered. The review concludes that children's participation must be formally integrated into practice, policy, and research to truly uphold their best interests